Improved spectrum sharing model in cognitive radios based on game theory - HUANG Li-ya; LIU Chen; WANG Suo-ping (Tongxin xuebao)
An improved spectrum sharing model was proposed in cognitive radios.The improved model considers com-prehensively impact on the primary users’ profits by all secondary users’ bandwidth requirement,and impact on every secondary user’s profit by other secondary users’ bandwidth requirement.Meanwhile,primary users in competition with secondary users can gain maximum profits by finding the optimal price of bandwidth,secondary users compete or coop-erate with each other can gain maximum profits by changing the required spectral bandwidths in limited spectrum.The simulation on features of this improved model,such as static game,dynamic game and its stability,Pareto optimal,has proved that this model adapts to the actual situation.